2016
DOI: 10.1515/jpm-2015-0404
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity in twins by birth order, gestational age and mode of delivery

Abstract: Mode of delivery and birth order have a gestational age dependent effect on the incidence of RDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…The response rate was 54%. Out of the 19 authors who responded, 14 could not provide the requested data [ 26 – 39 ], two authors contributed data we could not use [ 40 , 41 ], and three authors provided data we included in our meta-analyses [ 42 44 ]. The main reasons for not being able to include studies without author response were absence of stratification of data by gestational age < 28 weeks or birth weight < 1000 g, by birth order or by presentation in the original paper (Additional file 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The response rate was 54%. Out of the 19 authors who responded, 14 could not provide the requested data [ 26 – 39 ], two authors contributed data we could not use [ 40 , 41 ], and three authors provided data we included in our meta-analyses [ 42 44 ]. The main reasons for not being able to include studies without author response were absence of stratification of data by gestational age < 28 weeks or birth weight < 1000 g, by birth order or by presentation in the original paper (Additional file 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…All twins from Boukerrou [ 43 ] and Barzilay [ 44 ] were planned for active resuscitation. Bricelj 2016 [ 42 ] could not confirm active resuscitation for all twins, and therefore we included their data only for twins born at 25 +0 –27 +6 weeks in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This difference between the results of the two studies might be due to the large difference in sample size (114 vs. 679 twins in the Israeli and Korean groups, respectively). Other studies [12] seem to support the pessimistic view.…”
mentioning
confidence: 88%
“…Two other papers discuss the issue of "near term" (or the newer nomenclature "late preterm") births in twins, which bear a direct relationship to the clinical, albeit controversial, question of the appropriate timing of twin birth [12]. Simchen and her co-workers [13] observed that a significant proportion of late preterm (34 0/7-35 6/7 weeks) births is iatrogenic.…”
mentioning
confidence: 99%
“…As mães perceberam o gêmeo primogênito como mais dominante, menos dependente e com menos comportamentos relacionados a conflitos em comparação com o gêmeo que nasceu posteriormente, independentemente da zigosidade. Embora existam poucos estudos que tenham investigado o efeito da ordem de nascimento no relacionamento entre os gêmeos, há evidências de que o gêmeo primogênito tenha mais vantagens, como, por exemplo, maior peso ao nascer (Yokoyama et al, 2016) e menos complicações no nascimento (como síndrome de dificuldade respiratória) (Bricelj et al, 2016), que podem estar relacionadas a diferenças comportamentais nos anos posteriores. Esta relação entre peso corporal e possíveis indicadores de comportamentos de dominância entre gêmeos foi identificado no estudo observacional desenvolvido por Nakamichi (1983).…”
Section: Existe Diferença Entre Os Grupos De Irmãos Gêmeos E Não Gêmeos?unclassified